HUBUNGAN KARAKTERISTIK KEPENDUDUKAN DENGAN KESEJAHTERAAN KELUARGA DI PROVINSI JAMBI - Suandi, Suandi; Yuslidar, Yuslidar; Suma, Sudirman; Damayanti, Yusma (PIRAMIDA; Vol 10 No 2 (2014): Jurnal PIRAMIDA, 2014)
The objectives of this study is to analyze the relationship of demographic characteristics on well-being of households in rural areas Jambi Province. The research design is cross-sectional and was carried out in Kerinci, Sarolangun, Bungo, Tebo, Batanghari, Muaro Jambi, Tanjung Jabung Barat, and Tanjung Jabung Timur regency from July to November 2014. 2.600 households sample are chosen using purposive and random sampling methods. Descriptive, and Product Moment Correlation Test models were used for data analyzed. The results showed that the average of household expenditure levels in the study area is Rp. 4.504.421,16.- per month, and total expenditure per year is Rp.23,510,549,-. The expenditure is far above the average measure of well-being with the approach of the Central Bureau of Statistics (Rp.13.320.000,-). Demographic characteristics have a significant correlated on the pattern of housholds expenditure and well-being.
Keywords: demographic characteristics, adequacy of household consumption, household expenditures, and household well-being.